Kinerja Staf Organisasi dan Kepuasan Tamu dalam Industri Pariwisata di Indonesia - Witarsa Witarsa; I Made Darsana; I Made Sudjana; Wamaungo Juma Abdu (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
The waiter’s role is of great importance in the smooth operation of a restaurant business within the tourism industry. Thus, it is necessary to critically examine the waiter’s performance concerning guest satisfaction in a tourism organization. In the case of this study, a waiter not only performs the role of a waitress but is also tasked to become an ambassador within the sector. Taking Warung Mesari in the context of this study, waiters must display good hospitality in welcoming visitors and introducing and preserving the restaurant’s image. Based on this view, the present study looks at the performance of waiters as a way to contribute to the increament in the number of guests satisfied with the services provided by warung Mesari. The research method used is descriptive-qualitative, with data collection techniques in the form of interviews, documentation studies, and observations. This study revealed that: the waiters were able to provide good service and establish good relationships with guests who visited the restaurant; the waiters have done their job successfully; the restaurant has received many positive guest comments from guests; the restaurant also gets repeater guests; and guests who have visited again invite their friends to visit the Warung Mesari restaurant.